Establishing design criteria for the incorporation of highly glazed spaces into the domestic building envelope - Swann, Barbara (Cranfield University, 1996)
This thesis investigates the design of domestic glazed spaces in the United Kingdom, by studying the effect of a range of variables on the thermal properties of glazed spaces, in order to achieve a thermally comfortable environment while minimising the use of energy for heating and cooling. Earlier research work on domestic glazed spaces has concentrated on optimising the design of the space as a mechanism for reducing the space heating load of the parent house. Computer based dynamic thermal simulation is used in this study as the method of assessment and the variables tested are; glazing type, orientation and the degree of integration of the glazed space with the parent building. Unshaded, unventilated, and unheated, glazed spaces were found to be thermally comfortable for only a quarter to a third of the hours of possible use whatever the form, orientation or glazing type. Generally the higher the insulating value of the glazing the fewer the number of comfortable hours for all orientations and arrangements, due to discomfort being caused by high temperatures, even though the weather data used for the simulations only rose above 27'C for 25 hours during the course of the year. Further studies showed that significant reductions in the number of hours experiencing high temperatures could be achieved by the use of buoyancy driven ventilation. The studies indicated that glazed spaces integrated into the house plan tended to experience high temperatures for long periods but that the peak temperatures were much lower than those experienced for shorter periods in the exposed spaces. The effect of ventilation on overheating was therefore more marked in the integral than in the exposed glazed spaces. A study of the effects of roof shading blinds indicated that internal blinds had minimal effect in reducing high temperatures. External blinds had a greater effect than ventilation and a combination of external roof blinds and ventilation appears to provide the best strategy for the control of high temperatures. Studies on space heating loads for the houses and glazed spaces indicated wide variations in the heating loads of the glazed spaces depending predominantly on the insulating properties of the glazing. In terms of the reduction in the space heating load for the parent house, the thermal simulation results predict very little change due to the presence of the glazed space. A study on the effect of increasing the thermal storage properties of the floor construction of the glazed spaces, by substituting a clay tile finish for the original thin carpet layer, in order to reduce high temperatures proved inconclusive with minimal changes in the number of comfortable hours experienced. An investigation of thermal comfort during the Winter indicated that low surface temperatures did not reduce resultant temperatures below the lower limit of the comfortable range in the glazed spaces, during the heated period.